Community nurse-paramedics' sphere of practice in primary care; an ethnographic study - Rasku Tuija; Kaunonen Marja; Thyer Elizabeth; Paavilainen Eija; Joronen Katja (United Kingdom, 2022)
Background: Primary care, the principal function of the health care system, requires effort from all local primary health care teams. Community Paramedicine (CP) has managed to reduce the use of Emergency Medical Services (EMS) for non-emergency calls, but for the paramedic to move from traditional emergency calls to non-emergency care will mean new demands. There is a paucity of research exploring nurse-paramedics' experiences and perceptions of their novel roles as community paramedics in Finland. This study aims to explore the community nurse-paramedics' (CNP) experiences in their new sphere of practice.
Methods: A descriptive ethnographic study was conducted, to collect data through participant observation (317 h total) and semi-structured interviews (N = 22) in three hospital districts (HD) where the CNPs have worked for at least 1 year. Both data sets were combined, organised, and analysed using inductive content analysis.
Results: Five main categories were developed by applying inductive content analysis: the new way of thinking, the broad group of patients, the way to provide care, the diversity of multidisciplinary collaboration, and tailored support from the organisation. The CNP was identified as needing an appropriate attitude towards care and a broader way of thinking compared to the traditional practice of taking care of the patient and the family members. The diversity of multidisciplinary collaboration teams can be a sensitive but worthwhile topic for offering new possibilities. Tailored support from the organisation includes tools for future CP models.
Conclusions: Our results indicate the CNPs' deep involvement in patients' and families' care needs and challenges with their skills and competencies. Their professional attitudes and eagerness to develop and maintain multidisciplinary collaboration can offer preventive and long-term caring solutions from which citizens, allied health, safety, and social care providers benefit locally and globally.